The role of the Church in Lima during the war with Chile: An approximation to the pastoral letters and funeral prayers (1879-1883) - Cordero Bravo, César (2020)
The present article is divided in two parts: a preamble and the development of the information subject of study. In its first section, it is acknowledged the current absence of special chapters in most classic works on the War of the Pacific, dedicated to the role of religion. Having founded only four outstanding works, from the last century. Therefore, the importance of knowing what was the reaction and the role a religious corporation like the Catholic Church in Lima had throughout those five long years of conflict. Including the occupation of the city of Lima, capital of its archdiocese. In the second part, the pastoral field is presented as the first means the Church uses to make itself heard. Prominent members of Lima clergy wrote these letters and funeral prayers. The documents were written and/or proclaimed in the pulpits of temples, or published in newspapers of Lima and in the country. The letters and prayers represent a valuable source of information to learn about the Church’s theology and perception of the catastrophe of the war.